Pengaruh Multimedia Pembelajaran Terhadap Motivasi Dan Hasil Belajar Siswa Di Sd Negeri 122 Tassipi Kecamatan Amali Kabupaten Bone - Wildasari; Arismunandar; Muhammad Irfan (PT PUSTAKA CENDEKIA GROUP, 2025)
The formulation of the problem in this research is how to describe the implementation of learning using multimedia, description of motivation and the influence of using multimedia on student motivation and learning outcomes at SD Negeri 122 Tassipi, Amali District, Bone Regency. This research is an experimental research which aims to find out the description of the implementation of learning using multimedia in elementary schools. 122 Tassipi, Amali sub-district, Bone regency. The research approach is a quantitative approach. Research data was obtained through questionnaires and test sheets. The population in the study were all students at SDN 122 Tassipi, Amali subdistrict, Bone district. The sample in this research was 32 class IV students. The data analysis technique is descriptive and inferential statistical analysis. The results obtained in this research are an illustration of the influence of multimedia learning on student motivation and learning outcomes, especially in Class IV SDN 122 Tassipi, Amali subdistrict, Bone district.